Implementation of the “JASBUG” Mobile App as a Tool for Improving Students’ Physical Fitness - Arifah Kaharina; Muchamad Arif Al Ardha; Afifan Yulfadinata; Novadri Ayubi; Heryanto Nur Muhammad (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Abstract: Physical fitness among Indonesian junior high school students remains uneven, ranging from good to very poor categories across different schools and regions, including Surabaya, East Java. The Indonesian government addressed this issue by introducing the Tes Kebugaran Pelajar Nusantara (TKPN) as a standardized fitness assessment instrument, yet physical education teachers still face two major challenges: limited mastery of the new testing procedure and reliance on manual, error-prone score recording. This community service program trained and introduced the